EFFECT OF SALINITY ACCLIMATION ON FOOD INTAKE, DIGESTIBILITY AND EVACUATION RATE IN LIZA ABU JUVENILES - AHMED, S.M.; Mohamed, F.A.H.; AL-DUBAIKEL, A.Y. (Iraqi Journal of Aquaculture, 2022)
The results obtained for the juveniles of Liza abu showed that in high salinity there was a decrease in food intake (1.88%) compared to low salinity (7g/l) and tap water (1.5g/l). Also the total digestibility decreased 10% with increasing salinity from1.5 to 15 7g/l as a result of increasing the evacuation rate, where values reached 88.39% and 90.3% from total faces weight in salinity 7 and 15 g/l respectively after 18 hrs.